Cognitive disorder and associated factors among pregnant women attending antenatal service at Dilla University Referral Hospital, 2022 - Kassaw, Chalachew; Wale, Tiruwork; Negash, Misrak; Temesgen, Kiber; Mekuriaw, Birhanie; Tolessa, Omega; Abdisa, Elias Nigusu; Chekol, Yigrem Ali; Ayano, Getinet; Anbesaw, Tamrat (Frontiers in Global Women's Health, 2023)
Introduction: Cognition is defined as the mental activity or process of learning information and understanding through reason, experience, and the senses. In Sub-Saharan African nations like Ethiopia, such assessments of a pregnant mother's mental health during antenatal care is uncommon procedures and instead place a greater focus on the physical wellbeing of the woman and her fetus. As a result, the purpose of this study was to evaluate the cognitive deficits and related factors in a pregnant woman attending an antenatal service. Methodology: This hospital-based cross-sectional study included 415 pregnant women who were receiving antenatal care at Dilla referral hospital. In this study, respondents were chosen using systematic random sampling, and study participants were interviewed using administered questions to gather pertinent data. This study used the OSLO Social Support Scale, the Alcohol, Smoking, and Substance Involvement Screening Test, and the Mini-Mental Status Examination to assess the social support, cognitive status, and current substance use history of a respondent. Descriptive statistics including frequencies, graphs, and percentages were used to describe the results. A logistic regression analysis was conducted to determine the connection between independent factors and the outcome variable at a 95 percent confidence level and p 0.05. Result: Among all respondents who came for antenatal care visits, only 24(5.8%) were unmarried (single, divorced, widowed). The mean age of a respondent is 26 years old and 155(37.3%) of attended secondary school. Variables such as strong social support (0.11(0.03-0.23), P< 0.02), orthodox religion follower (0.24(0.12-0.39), p< 0.04), > 5000 Ethiopian birr monthly income (0.28(0.17-0.48), P< 0.02), age > 26 years old (1.23(1.14-2.54), p<0.04), un-planed pregnancy (2.78(1.45-4.32), p<0.02) and rural residence (3.90(2.23-7.34), p<0.04) were significantly associated with cognitive disorder at 95% confidence interval and P<0.05. Conclusion: This study found that pregnant women who attended antenatal care experienced a significant reduction in cognitive function. Additionally, this study revealed flexible elements such as unintended pregnancies, social support, and religiosity. Therefore, it is preferable to check a pregnant woman's cognitive condition as she arrives for follow-up on each follow-up segment.